Anthocyanin Partition in Aqueous Two‐Phase Systems Based on Isopropanol and Sodium/Ammonium Sulfate. Issue 9 (3rd August 2022) - Caldeira, Ana Clara Rocha; Converti, Attilio; Naves deMoraes, Moysés; Teles deFaria, Janaína
Abstract: Partitioning of anthocyanins contained in the crude extract of Syzygium cumini fruit was investigated in aqueous two‐phase systems (ATPS) made up of isopropanol and Na2 SO4 /(NH4 )2 SO4 . Na2 SO4 induced ATPS formation more effectively than (NH4 )2 SO4 . The increase in temperature enhanced phase separation in the (NH4 )2 SO4 ATPS, while the opposite occurred in the Na2 SO4 ATPS. The higher the overall mixture concentration or temperature, the higher the values of tie‐line length and slope. In all systems and conditions, anthocyanins preferentially partitioned to the top phase. The partition coefficient and theoretical recovery yield in the top phase varied in the ranges 1.14–1.77 and 53.31–63.87 % in the (NH4 )2 SO4 ATPS, and in the ranges 1.94–21.50 and 65.90–95.55 % in the Na2 SO4 ATPS. Abstract : A crude Syzygium cumini fruit extract was treated with isopropanol‐Na2 SO4 or (NH4 )2 SO4 aqueous two‐phase systems. The effects of salt, tie‐line length, and temperature on liquid‐liquid phase behavior and anthocyanin partition were investigated. Anthocyanins partitioned mainly to the alcohol‐rich phase of Na2 SO4 systems, which may be used in a preliminary step of the recovery of anthocyanins.